Survival beyond the perinatal period expands the phenotypes caused by mutations in GLE1. Issue 11 (8th September 2017) - Said, Edith; Chong, Jessica X.; Hempel, Maja; Denecke, Jonas; Soler, Paul; Strom, Tim; Nickerson, Deborah A.; Kubisch, Christian; ,; Bamshad, Michael J.; Lessel, Davor
Abstract : Mutations in GLE1 underlie Lethal Congenital Contracture syndrome (LCCS) and Lethal Arthrogryposis with Anterior Horn Cell Disease (LAAHD). Both LCCS and LAAHD are characterized by reduced fetal movements, congenital contractures, and a severe form of motor neuron disease that results in fetal death or death in the perinatal period, respectively. We identified bi‐allelic mutations in GLE1 in two unrelated individuals with motor delays, feeding difficulties, and respiratory insufficiency who survived beyond the perinatal period. Each affected child had missense variants predicted to result in amino acid substitutions near the C‐terminus of GLE1 that are predicted to disrupt protein–protein interaction or GLE1 protein targeting. We hypothesize that mutations that preserve function of the coiled‐coil domain of GLE1 cause LAAHD whereas mutations that abolish the function of the coiled‐coil domain cause LCCS. The phenotype of LAAHD is now expanded to include multiple individuals surviving into childhood suggesting that LAAHD is a misnomer and should be re‐named Arthrogryposis with Anterior Horn Cell Disease (AAHD).